The Drama of Existence: Myths and Rituals in Wole Soyinka's Theatre - Figueiredo, Rosa Branca (2016)
Traditional African expressive and performance forms like myths and rituals, dance and mime, music and masquerade. Diverse Western dramatic and theatrical modes such as classical Greek drama, Shakespearean and Jacobean theatre and modern European and American antirealist and avant~garde forms and techniques